2020
DOI: 10.1590/s2175-97902019000417835
|View full text |Cite
|
Sign up to set email alerts
|

Is dialysis water a safe component for hemodialysis treatment in São Paulo State, Brazil?

Abstract: Failure on the water treatment poses hemodialysis patients at risk of injury and death. Identifying if the patients are exposed to water quality related microbiological risks is an important objective to reduce the mortality for chronic renal patients and is the main issue of this study. We evaluated the microbiological water quality used by 205 dialysis services in São Paulo State, Brazil between 2010 to 2016. The study included heterotrophic bacteria count, total coliforms research, and bacterial endotoxin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
4
0
3
Order By: Relevance
“…In this research, around 30% of the samples of post-RO water and 13% of dialysate samples presented unconforming parameters regarding the THB recommended. Comparatively, studies in the southeastern region of Brazil, which assessed a larger number of hemodialysis units, a more extended period, and a greater number of samples, indicated higher non-compliance rates, ranging from 27% to 63% (Hilinski et al, 2020). In contrast, other investigations, also encompassing a broader sampling, reported lower rates, ranging from 5% to 8% (Almodovar et al, 2018).…”
Section: Bacteriological Parametersmentioning
confidence: 81%
See 1 more Smart Citation
“…In this research, around 30% of the samples of post-RO water and 13% of dialysate samples presented unconforming parameters regarding the THB recommended. Comparatively, studies in the southeastern region of Brazil, which assessed a larger number of hemodialysis units, a more extended period, and a greater number of samples, indicated higher non-compliance rates, ranging from 27% to 63% (Hilinski et al, 2020). In contrast, other investigations, also encompassing a broader sampling, reported lower rates, ranging from 5% to 8% (Almodovar et al, 2018).…”
Section: Bacteriological Parametersmentioning
confidence: 81%
“…Despite established guidelines, studies conducted in Brazil reveal dissatisfaction levels regarding certain parameters of water quality intended for hemodialysis, such as high levels of heterotrophic bacteria, elevated concentrations of endotoxins (Almodovar et al, 2018;Hilinski et al, 2020;de Jesus et al, 2022), and the significant presence of aluminum (de Jesus et al, 2022). Additionally, some studies report the presence of fungi in these waters, posing potential risks to the health of hemodialysis patients (Montanari et al, 2018;Oliveira et al, 2018;Anversa et al, 2021;Calumby et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The acceptable international maximum allowable level of bacteria (˂100 CFU/ml) or the action level (˂50 CFU/ml) (ANSI/AAMI 23500 2019; ISO 23500 2019). To keep the bacterial count below the action level, a regular and effective disinfection procedure must be performed as part of the hygienic maintenance of the water treatment units (Hilinski et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 10 - 12 In another study conducted by Suzuki et al 13 on the quality of dialysis water in Brazil, it was found that the concentration of copper, nitrate and aluminum in dialysis water is higher than the standard limits. The studies of Abualhasan et al 7 in Palestine, Vorbeck-Meister et al 14 in Vienna, Austria, Hilinski et al 15 in Brazil, Ocunola and Olaitan 16 in Nigeria and Jesus et al 17 in Riode Jeneiro, Brezil also showed that the quality of water used for hemodialysis patients was not up to standard.…”
Section: Introductionmentioning
confidence: 99%